South East Europe Hub and Spoke Air Network Reconfiguration - Pavlin, Stanislav; Modić, Arijana; Bračić, Matija (Promet - Traffic&Transportation, 2017)
The paper presents the passenger and cargo historical traffic data analysis at the Zagreb Airport, at certain airports in the wider region and globally for a period of half a century. The war during 1990s and the disintegration of Yugoslavia had as a consequence the breakdown of air transport based on hub and spoke system with three airports as a hub: Zagreb, Belgrade and Ljubljana. During and after the war, the domestic airliner in the region and a foreign airliner implemented primarily point-to-point system. Hub airports have become origin-destination airports with mainly local passengers and insignificant ratio of transfer and transit passengers. The causes of slow passenger and cargo traffic growth at the Zagreb Airport and of passengers at certain airports in the narrow region have been analysed and the results are lower growth of air traffic at capital airports of the new countries and greater air traffic growth on the capital airports and others in the countries of a wide region comparing with the global passenger transport growth. The paper indicates the possible measures to increase the share of transfer passengers and cargo traffic at the Zagreb Airport and certain airports in the immediate region.